Produção de hidrogênio e etanol através da fermentação acidogênica de águas residuárias agroindustriais em reator anaeróbio de leito fluidizado - Rosa, Paula Rúbia Ferreira (2014)
The aim of this study was to evaluate the influence of hydraulic retention time (HRT), the origin of different inoculum (sludge from a UASB reactor for swine wastewater treatment and poultry slaughterhouse), and different carbon source (glucose, cassava processing wastewater and cheese whey) on the stability and efficiency of the anaerobic fluidized bed reactor (AFBR) for producing hydrogen. Twelve identical reactors were used, and in two reactors the mixture of glucose with cheese whey (R1S, R2S) was used as a substrate, six reactors were used with mix cassava processing wastewater and glucose (R1M, R2M, R3M and R4M). It was evaluated use of cheese whey (R3S, R4S, R5s and R6S) and cassava processing wastewater (R5M and R6M). The AFBRs were inoculated with sludge from a UASB reactor used in the treatment of swine wastewater (R1S, R3S, R1M, R3M, R5S, R6S, R5M and R6M) and sludge from a UASB reactor that treated poultry slaughterhouse wastewater (R2S, R4S, R2M, R4M), both heat treated. Variations of HRT (12-1 h) and substrate concentrations were performed (2-15 g .L -1), with temperature control at 30 ° C. The reactors that used cheese whey as substrate showed a greatest potential for hydrogen production, with yields (HY) of 3.2 mmolH2.g-1COD (R6S) and 2.6 mmolH2.g-1COD (R5S) were obtained by applying a HRT of 6 and 14 hours, with a concentration of 3 and 5 g.L-1, respectively. Both substrates showed potential for the production of ethanol with yields (EtOHY) of 4.2 mmolEtOH.g-1COD (R6M) and 3.5 mmolEtOH.g-1COD (R2S). In the comparison between the two inocula used, both showed a balance in terms of hydrogen production, but in terms of ethanol production, the sludge from poultry slaughterhouse showed highest potential. By cloning and sequencing of the 16S rRNA gene for bacteria domain reactor R4S (whey), there was a predominance of the genus Selenomonas (69 % of the sequences) and Clostridium (8 % of the sequences). For the reactor R3M (glucose and cassava) analyzes cloning and sequencing of bacterial consortium revealed similarities with Lactobaccilus. As for the archaeal domain, the sequencing of the 16S rRNA gene had highly similar to the genus Methanobacterium (98.5 % and 95 % of the sequences), for R4S and R3M, respectively reactors.